Play and Spiel are not the Same: Anti-Wittgensteinian Arguments and Consideration of Game as a Kind of Human Play. Issue 6 (September 2021) - Lebed, Felix
The differences between categories of play in English and spiel in German (or jeu in French and so on) are essential because any complex ludic category includes games that are organized and restricted by roles and rules. My choice to deal with Wittgensteinian views of spiel (which is translated by default as 'play') is influenced by the fact that his argument in German about the impossibility and futility of a philosophical definition of spiel embodies the quintessence of the problem: the linguistic obstacle that prevents correct interpretation of human play. Methodologically, I make the philosophical question of dependence a linguistic one. The article concludes by defending the position that game is only one of the diverse activities realizing human play, which is a basic existential phenomenon that can be considered philosophically through the category of 'other being'.